Progressive collapse behaviour of precast concrete structures with advanced joints - Nguyen, Van Hung (Nanyang Technological University, 2024)
Progressive collapse, where widespread structural failure is triggered by localised failures, is regarded as a critical concern. In this context, offering a threat-independent approach, the alternate load path (ALP) method simplifies progressive collapse analysis by considering a single-column removal scenario. However, most ALP studies primarily concentrated on reinforced concrete (RC) or precast concrete (PC) structures with convential joint detailing, leaving a knowledge gap in understanding of progressive collapse of precast concrete (PC) structures with wet connections and special joint detailing. This knowledge gap motivates research into static behaviour of the PC substructures against progressive collapse. To improve inaccuracy in previous model predictions of structural response, a refined component-based model (CBM) was proposed for RC frames with conventional and special joint detailing against progressive collapse. Through numerical analysis, advantages of incorporating an additional bar layer (ABL) and plastic hinge relocation (PHR) in the beam-joint region for enhancing collapse resistance of RC frames were illuminated. To verify these findings, three types of PC wet joints, employing (i) headed bars (Type H), (ii) providing an ABL (Type A), and (iii) incorporating PHR with X-bent bar (Type X) in the beam-joint region, were developed. Subsequently, two sets of static tests on these joints (Series I and II), along with a component pull-out test on headed bars, were conducted. In Series I, progressive collapse of four interior joints under a middle column removal scenario (MCRS) was investigated, ultimately confirming practical feasibility of the proposed joint detailing. In addition to flexural action, compressive arch action (CAA) and catenary action (CA) were mobilised against collapse. Moreover, superior collapse resistance of Type X compared to Type H and Type A joints was observed. Secondly, the pull-out test results highlighted a pivotal role of bearing force in anchorage strength of headed bars and strain behaviour. Building upon this insight, a macro bond-slip model was proposed for headed bars, incorporated into CBMs, and verified against the test results from Series I with reasonable accuracy. A parametric study based on the verified model shed light on collapse behaviour of penultimate joints under a penultimate exterior column removal scenario (PECRS). In addition to test Series I, the experimental programme in Series II focused on progressive collapse behaviour of exterior joints. This series involved two exterior joint specimens, both subjected to a PECRS. The investigations in Series I and II provided insights into progressive collapse behaviour of interior and exterior PC joints. However, understanding progressive collapse behaviour in the context of a building structure is vital for robustness and mitigation. Hence, a simplified finite element model was proposed, integrating joint-level findings from Series I and II to examine the overall response of a PC building following progressive collapse. Moreover, the impact of slab contribution, level of removed column, column removal scenarios, and modelling technique on progressive collapse behaviour of PC structures was shed light.